2014
DOI: 10.1093/gbe/evu141
|View full text |Cite
|
Sign up to set email alerts
|

Specific Activation of an I-Like Element in Drosophila Interspecific Hybrids

Abstract: The non-long terminal repeat (LTR) retrotransposon I, which belongs to the I superfamily of non-LTR retrotransposons, is well known in Drosophila because it transposes at a high frequency in the female germline cells in I–R hybrid dysgenic crosses of Drosophila melanogaster. Here, we report the occurrence and the upregulation of an I-like element in the hybrids of two sister species belonging to the repleta group of the genus Drosophila, D. mojavensis, and D. arizonae. These two species display variable degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…However, TE expression variation between reciprocal hybrids in the female germ line stresses the necessity of further population studies in order to investigate whether these mobile elements might contribute to post-zygotic reproductive isolation between D. mojavensis and D. arizonae . We have shown that some specific TEs are upregulated in the male germline depending on the source population of males and females, and the direction of the cross53. Thus, sterility in males could be associated with the mobilization of TEs and a transcritome analysis of the male germ line is needed because it could explain why TEs, despite a strong negative selection against deleterious transposition effects, remain successfully active in the male line.…”
Section: Discussionmentioning
confidence: 99%
“…However, TE expression variation between reciprocal hybrids in the female germ line stresses the necessity of further population studies in order to investigate whether these mobile elements might contribute to post-zygotic reproductive isolation between D. mojavensis and D. arizonae . We have shown that some specific TEs are upregulated in the male germline depending on the source population of males and females, and the direction of the cross53. Thus, sterility in males could be associated with the mobilization of TEs and a transcritome analysis of the male germ line is needed because it could explain why TEs, despite a strong negative selection against deleterious transposition effects, remain successfully active in the male line.…”
Section: Discussionmentioning
confidence: 99%
“…(). The TD was conducted combining methods from previous studies (Akkouche et al., ; Carnelossi et al., ; Munroe et al., ; Roy et al., ). First, individual extracted DNA (≈ 75 ng) was used for enzymatic digestion in a total volume of 20 μl, with HindIII enzyme (10 U/μl) and buffer R (Thermo Scientific) for 3 hr at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The total DNA was extracted from whole adult bodies following the phenol-chloroform protocol described by Minard et al (2015). The TD was conducted combining methods from previous studies (Akkouche et al, 2012;Carnelossi et al, 2014;Munroe et al, 1994;Roy et al, 1999). First, individual extracted DNA (% 75 ng) was used for enzymatic digestion in a total volume of 20 ll, with HindIII enzyme (10 U/ll) and buffer R (Thermo Scientific) for 3 hr at 37°C.…”
Section: Dna Extraction and Td Adapter Ligationmentioning
confidence: 99%
“…Transposable elements (TEs) may play an outsized role in establishing such incompatibilities because of their ability to rapidly proliferate. Studies of hybridization across diverse systems have revealed complex patterns of increased TE expression and transposition in hybrids [4][5][6][7][8][9][10][11][12]. However, it is not clear if increased TE activity is a general response to hybridization.…”
Section: Introductionmentioning
confidence: 99%